Addressing Writing Deficiencies: Innovative Strategies for Enhancing English Writing Skills Among Junior Secondary School Students in Jigawa State (British Journal of Multidisciplinary and Advanced Studies, 2025)
This study investigates strategies to improve English writing proficiency among junior secondary school students in Jigawa State, Nigeria. Writing in English poses significant challenges for students, resulting from limited vocabulary, inadequate teaching methods, and a lack of confidence. The study employed a mixed-methods approach, combining surveys and interviews with 300 students and 30 teachers to identify key challenges and evaluate current instructional practices. An intervention involving peer feedback, process writing, and mentor texts was implemented over a 10-week period. Pre- and post-test evaluations showed a significant improvement in students’ writing proficiency, with average scores increasing from 38% to 65%. Students also demonstrated increased confidence and engagement in writing tasks. Teachers reported that structured writing processes and collaborative learning were particularly effective in enhancing students' ability to organize their thoughts and apply grammatical rules. The study concludes that integrating these strategies into the English language curriculum can substantially improve writing skills and overall academic performance. Recommendations for policy and future research are also provided.